Recent Advances in Aggregation-Induced Emission (AIE) Fluorescent Sensors for Biomolecule Detection - Kavya S. Keremane; M. Gururaj Acharya; Praveen Naik; Chandi C. Malakar; Kai Wang; Bed Poudel (Chemosensors)
Fluorescent sensors are indispensable tools in fields such as molecular biology, clinical diagnostics, biotechnology, and environmental monitoring, due to their high sensitivity, selectivity, biocompatibility, rapid response, and ease of use. However, conventional fluorophores often suffer from aggregation-caused quenching (ACQ), leading to diminished fluorescence in the aggregated state. The advent of aggregation-induced emission (AIE) luminogens, which exhibit enhanced fluorescence upon aggregation, offers a powerful solution to this limitation. Their unique photophysical properties have made AIE-based materials highly valuable for diverse applications, including biomedical imaging, optoelectronics, stimuli-responsive systems, drug delivery, and chemical sensing. Notably, AIE-based fluorescent probes are emerging as attractive alternatives to traditional analytical methods owing to their low cost, fast detection, and high selectivity. Over the past two decades, considerable progress has been made in the rational design and development of AIE-active small-molecule fluorescent probes for detecting a wide variety of analytes, such as biologically relevant molecules, drug compounds, volatile organic compounds (VOCs), explosives, and contaminants associated with forensic and food safety analysis. This review highlights recent advances in organic AIE-based fluorescent probes, beginning with the fundamentals of AIE and typical “turn-on” sensing mechanisms, and concluding with a discussion of current challenges and future opportunities in this rapidly evolving research area.